A Legal Review of the Natuna Sea Dispute Between Indonesia and China in International Law - Afrian Tama Syahputra; Diki Zukriadi (Sean Institute, 2025)
This article aims to analyze the ongoing negotiations between Indonesia and China regarding the Natuna Islands from the perspective of international law. As a maritime nation comprising over 17,000 islands, Indonesia possesses vast territorial waters and abundant natural resources, including fisheries, minerals, and hydrocarbons. These assets render territorial disputes inevitable, particularly in contested maritime zones. The Natuna Islands, located in the northern part of Indonesia's exclusive economic zone (EEZ), have emerged as a focal point of contention with China, whose expansive claims in the South China Sea overlap with Indonesia's sovereign rights. The dispute stems from China's assertion of historical rights over the South China Sea, encapsulated in its